Magnetically Actuated Microscaffold with Controllable Magnetization and Morphology for Regeneration of Osteochondral Tissue - Junhyeok Lee; Hyeong-Woo Song; Kim Tien Nguyen; Seokjae Kim; Minghui Nan; Jong-Oh Park; Gwangjun Go; Eunpyo Choi (Micromachines, 2023)
Magnetic microscaffolds capable of targeted cell delivery have been developed for tissue regeneration. However, the microscaffolds developed so far with similar morphologies have limitations for applications to osteochondral disease, which requires simultaneous treatment of the cartilage and subchondral bone. This study proposes magnetically actuated microscaffolds tailored to the cartilage and subchondral bone for osteochondral tissue regeneration, named magnetically actuated microscaffolds for cartilage regeneration (MAM-CR) and for subchondral bone regeneration (MAM-SBR). The morphologies of the microscaffolds were controlled using a double emulsion and microfluidic flow. In addition, due to their different sizes, MAM-CR and MAM-SBR have different magnetizations because of the different amounts of magnetic nanoparticles attached to their surfaces. In terms of biocompatibility, both microscaffolds were shown to grow cells without toxicity as potential cell carriers. In magnetic actuation tests of the microscaffolds, the relatively larger MAM-SBR moved faster than the MAM-CR under the same magnetic field strength. In a feasibility test, the magnetic targeting of the microscaffolds in 3D knee cartilage phantoms showed that the MAM-SBR and MAM-CR were sequentially moved to the target sites. Thus, the proposed magnetically actuated microscaffolds provide noninvasive treatment for osteochondral tissue disease.